Law Enforcement Information Technology: A Managerial, Operational, and Practitioner Guide - Chu, James (CRC Press, 2009)
ARE YOU PREPARED FOR THE LAW ENFORCEMENT IT REVOLUTION? Law enforcement agencies that are laggards in Information Technology (IT) will soon, if not already, be considered mismanaged. Whether you are in an operational position, or you are a police officer who aspires to a higher rank, you must be aware of how IT can help you perform your job and help your organization.